Korea's Rapid Export Expansion in the 1960s: How It Began - Jung Ho Yoo (KDI Journal of Economic Policy, 2017)
Korea's rapid export expansion suddenly began in the early 1960s and boosted the economy. This paper's investigation finds that it began in 1961, as new export items appeared, export of which increased incomparably faster than that of the current export items at the time. How and why of this highly unusual phenomenon can best be explained by a major reform of foreign exchange system in February 1961. This goes against the widely held view that the switch in development policy from import substitution to export promotion in the mid-1960s was the reason for Korea's export success. Rather, the evidence indicates that the rapid export expansion led to the policy switch. The government's export promotion since the policy switch helped the rapid export expansion continue into the 1970s, despite the protectionist import policy.
Keywords: O24; O25; O53; 330; Exchange Rate Policy; Trade Policy; Export Promotion; Comparative Advantage; Import Substitution